Partnerstwa zagraniczne polskich gmin - Ziółkowski, Marek (Foreign Partnership of Polish Communities, 2006)
The matter of this study is to describe the problem of foreign partnership of Polish communities. The results of the inquiry, which was carried out in Polish communities by TNS OBOP in the year 2000, are discussed against the background of general debate concerning legal-political basis of this cooperation and work of the European Union for the benefit of partnership cooperation of European communities. Characterization of partner relationship of Polish communities (forms and acting range) was also presented and main barriers which limit this cooperation were also pointed out. Basic conclusion which results from the analysis is that against the background of the rest of EU member countries the cooperation of Polish communities is still very poor. Only approximately half of all Polish communities have foreign partners. There are still many local governments, especially rural, which do not see any sense in acting in this way. Their representatives present often very passive behaviour in this matter.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 274-283